Parameter optimization and experiment of the negative pressure precision seed-metering device for wheat - Feng, Yubo; Zhao, Xiaoshun; Li, Jincai; Yu, Huali; Zhao, Hongpeng; Yin, Baozhong (International Journal of Agricultural and Biological Engineering, 2024)
In order to ensure the most reasonable distribution of wheat seeds in the field to improve seeding quality and uniformity, a set of negative pressure precision seed-metering device was designed, which shares a hollow shaft. Every seed-metering device can sow two rows of wheat. By the STAR-CCM+, the analysis of nephogram, vectogram and streamline graph showed that more ideal structural parameters of the seed-metering device are 0.5 mm width of the slit sucking seed (WSS), 150-200 mm diameter of the seed-metering disc (DSD), 2.0 mm axial depth of air chamber in the seed-metering disc (ADS), and arc-shaped cross-section shape of the ring groove sucking seed (CSGS). Single-factor test on the JPS-12 test-bed analyzed the influence of the CSGS, WSS, DSD, and ADS on the qualified index (Iq), multiple index (Imul), miss index (Imiss) and coefficient of variation of qualified seed spacing (CV). Through the orthogonal on the JPS-12 test-bed, it is found that the influence of vacuum negative pressure and seed-metering device shaft speed is significant on the Iq, Imiss and Imul. Based on these, the structural parameters of the seed-metering device were optimized. The DSD is 180 mm, the WSS is 0.7 mm, the ADS is 2.5 mm, and the CSGS is arc-shaped. The optimization seed-metering device was tested on the JPS-12 test-bed. The Iq is 86.66%, the Imiss is 5.09%, the Imul is 8.25%, and the CV is 24.50%. These testing results fully coincide with the standard JB/T 10293-2013 Specifications of single seed drill (precision drill). The seed-metering device meets fully the requirements for wheat precision seeding.Keywords: wheat, seed-metering device, negative pressure, precision, parameter optimization, STAR-CCM+, orthogonal test, variance analysisDOI: 10.25165/j.ijabe.20241701.8222Citation: Feng Y B, Zhao X S, Li J C, Yu H L, Zhao H P, Yin B Z. Parameter optimization and experiment of the negative pressure precision seed-metering device for wheat. Int J Agric & Biol Eng, 2024; 17(1): 154-162.